The effect of hydrostatic carbon dioxide pressure and extracellular ethanol on the performance of the yeast strain Saccharomyces cerevisiae during fermentation - Longden, Nicholas Guy (Rhodes University, Faculty of Science, Department of Biochemistry, Microbiology and Biotechnology, 1993)
The brewing industry constantly experiences problems in trying to maintain the quality of beer produced. Unfavourable conditions during fermentation may alter the performance of the yeast strain Saccharomyces cerevisiae, resulting in a "poor" end-product. It has been established that high concentrations of extracellular ethanol, when added to the fermentation medium inhibit yeast activity. It has been recently suggested that increased carbon dioxide pressure could inactivate the yeast activity adding to further brewing problems. The aim of this study was to investigate the effect of extracellular carbon dioxide pressure and ethanol addition, on yeast performance when added to a fermentation medium, and to establish whether an inhibitory relationship existed between ethanol and carbon dioxide pressure, when combined and added to the fermentation medium. Dissolved C0₂ in the medium, medium pH and substrate utilisation were analysed daily during a fermentation, as were membrane fatty acid composition. These parameters were used to assess the effect of ethanol and carbon dioxide on the yeast performance and consequently the final end-product. Supplementing the medium with extracellular ethanol, even as low as 5%, was shown to inhibit yeast performance during fermentation. This effect was even more marked as the ethanol concentration was increased, with almost total inhibition of yeast activity occuring after the addition of 15% ethanol (v/v). A similar effect was observed when elevated C0₂ pressures were applied to the medium, and although low C0₂ pressures initially induced the synthesis of saturated yeast membrane fatty acids, elevated C0₂ pressures (greater than 1,0 atm.) was shown to follow a similar inhibitory trend, if not as dramatic, as ethanol. A combination of both ethanol and C0₂ pressure showed a further increase in the level of yeast inhibition, although the low C0₂ pressure appeared to initially inhibit the toxicity of ethanol on the yeast. Increasing the levels of the C0₂/ethanol treatment (1,0 atm.), showed a synergistic effect on yeast performance. The results of this study indicate that both extracellular ethanol and carbon dioxide do appear to inhibit yeast performance and affect membrane fatty acid composition of the cells by inhibiting the synthesis of the respective fatty acid. This affect has a significant bearing on the general metabolism of the yeast cell.
Keywords: Brewing -- Microbiology; Yeast; Fermentation; Saccharomyces cerevisiae